Efektivitas Grammarly sebagai Alat Bantu Pembelajaran Keterampilan Menulis bagi Mahasiswa - Lesty, Merby Ariana; Assidik, Gallant Karunia (Universitas Negeri Padang, 2025)
Problems often faced by students are related to the inconsistency of words or sentences in writing, lack of attention to the writing structure following EYD (Enhanced Spelling), and often combining standard language with slang. This study aims to describe the effectiveness of Grammarly as a learning application accessed individually. However, it can be used to collaborate in solving problems in each sentence in writing. The research used is quantitative based on the experimental method. The research design includes a quasi-experimental design. The results show the effectiveness of using Grammarly on writing skills for students, as evidenced by the reliability test results, which showed a value of 0.764 so the data is declared reliable. Furthermore, the results of the normality test for the Asymp.Sig. (2-tailed) value is 0.200, so that the data is declared normally distributed. Then, the homogeneity test results are based on the sig value of 0.083> 0.05, so the data shows homogeneity. Finally, the hypothesis test results in Asymp.Sig. (2-sided) are 0.000, so that the data shows an accepted hypothesis. The data analysis results show that Grammarly is a practical learning application for improving sentences and avoiding grammatical errors.